2004
DOI: 10.1086/423857
|View full text |Cite
|
Sign up to set email alerts
|

A Major Lung Cancer Susceptibility Locus Maps to Chromosome 6q23–25

Abstract: Lung cancer is a major cause of death in the United States and other countries. The risk of lung cancer is greatly increased by cigarette smoking and by certain occupational exposures, but familial factors also clearly play a major role. To identify susceptibility genes for familial lung cancer, we conducted a genomewide linkage analysis of 52 extended pedigrees ascertained through probands with lung cancer who had several first-degree relatives with the same disease. Multipoint linkage analysis, under a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
181
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(200 citation statements)
references
References 69 publications
6
181
2
4
Order By: Relevance
“…Ultimately, verification of a genetic predisposition must come from the identification of causal mutations. Recently, following a genomewide linkage scan, a candidate locus for lung cancer predisposition has been reported (Bailey-Wilson et al, 2004). If confirmed, this would provide the most convincing evidence to date of a genetic susceptibility outside rare Mendelian disorders.…”
Section: Discussionmentioning
confidence: 87%
“…Ultimately, verification of a genetic predisposition must come from the identification of causal mutations. Recently, following a genomewide linkage scan, a candidate locus for lung cancer predisposition has been reported (Bailey-Wilson et al, 2004). If confirmed, this would provide the most convincing evidence to date of a genetic susceptibility outside rare Mendelian disorders.…”
Section: Discussionmentioning
confidence: 87%
“…A recent study in Detroit, Michigan [19] found an increased risk for early-onset lung cancer among those with a first-degree relative with lung cancer after adjusting for race, age, sex, and pack-years of smoking (OR=1.71, 95% CI=1.16-2.52). With regard to the genetic component of such familial risk, a susceptibility locus for lung cancer has recently been identified on chromosome six [20].…”
Section: Discussionmentioning
confidence: 99%
“…Family linkage studies have been used to identify genes for lung cancer, lung function, and COPD (30)(31)(32). The only linkage study in lung cancer successfully identified a region on 6q24 linked to familial lung cancer (30,33).…”
Section: Family Linkage Studiesmentioning
confidence: 99%
“…The only linkage study in lung cancer successfully identified a region on 6q24 linked to familial lung cancer (30,33). With fine mapping, the RGS17 gene was identified as a putative lung cancer susceptibility gene (34).…”
Section: Family Linkage Studiesmentioning
confidence: 99%